Faculty Development Tutorial System of the Academic Pediatric Association Educational Guidelines (Out of Print) - Constance Baldwin; Diane Kittredge; Miriam Bar-on; Franklin Trimm; Patricia Beach; Carol Carraccio (Association of American Medical Colleges, 2009)
Abstract Reorganizing curricula to meet competency-based requirements is a challenge for residency and fellowship programs. Building a new curriculum is not easy, and confusion about what exactly is required and then how to meet those requirements has frustrated many program leaders. The ACGME Outcome Project was launched before real solutions to the problem of evaluating competencies of residents had been solved. The Faculty Development Tutorial system was created to help residency educators meet these challenges, particularly educators using the Educational Guidelines for Pediatric Residency website, which provides the platform for these tutorials. This website is a curriculum-building resource for pediatric residency programs, but the tutorials contain information valuable to educators from any discipline. The tutorials are brief, practical, and focused on the key challenges of competency-based curriculum development. They can be used independently of the Educational Guidelines and are not specific to pediatrics. Users must create a username and password to log on. Otherwise access is cost-free and not restricted in any way. Once inside the website, users go to the Menu of Options, and there click on Tutorials to access the system. The Faculty Development Tutorial System webpage includes a separate instruction set called "How to Use This Faculty Development Tutorial System," six tutorial modules, and a dictionary of terms and concepts. The modules are presented in two formats: MS Word for screen-reading or downloading and MS PowerPoint for downloading to use in faculty development presentations. Customization of all the tutorial files after downloading from the website is encouraged. The six modules are organized around the elements of a planned curriculum: using goals and objectives to plan whole programs and rotations (Modules 2 and 3), planning learning experiences (Module 4), evaluating residents (Module 5), and evaluating programs (Module 6). The supplementary resource called "Medical Education Terms and Concepts" is electronically linked to the tutorials through clickable terms that occur throughout the modules. Data collected online show that during the 30 months after completion of the Guidelines, 1,129 tutorial files were downloaded from the website, with about equal numbers of Word and PowerPoint files. Tutorial users come from 50% of pediatric residency programs nationwide. Comments from tutorial users suggest varied and creative use of the modules.